470 Percutaneous arterial closure devices and ultrasound-guided trans-femoral puncture observational investigation: insights from the PETRONIO registry. (8th December 2021) - Iannopollo, Gianmarco; Nobile, Giampiero; Lanzilotti, Valerio; Capecchi, Alessandro; Verardi, Roberto; Bruno, Matteo; Somaschini, Alberto; Rubboli, Andrea; Pasquale, Giuseppe Di; Casella, Gianni
Abstract: Aims: To evaluate the safety of a single and combined use of ultrasound-guided femoral puncture (U) and percutaneous arterial closure devices (P) in femoral artery procedures (FAP) compared to fluoroscopic guidance (F) and manual compression (M) in a large radial-focused interventional centre. U and P, taken individually, have improved safety in femoral arterial access procedures compared to traditional techniques. Methods and results: All FAP performed between July 2017 and December 2018 in our centre were divided into three phases: (i) control period with F and M mainly performed; (ii) phase out period where U and P were introduced; and (iii) intervention period where a 6-month expertise on the novel techniques was acquired. The overall population was further stratified into subgroups: F/M, U/M, F/P, and U/P. The primary study endpoint was in-hospital access site bleeding events (BE) according to the BARC criteria. The secondary endpoint was vascular site complications (VASC). 418 procedures (14%) out of 3025 were performed via FA access during the study period. The overall access-site in-hospital BE were 97 (23%). Decreasing rates of BE (phase 1: n = 46, 29%; phase 2: n = 38, 22% e phase 3: n = 13, 15%; P = 0.027) and VASC were observed during the three periods. BE occurred significantly more often in F/M group (F/M: n = 48; 32%; U/M: n = 12, 16%; F/P: n = 18, 21%; U/P: n = 19, 17%; P = 0.008). F/M subgroup was an independent predictor of BE both in multivariable analysis and propensity score matching analysis. Conclusions: The introduction of ultrasound-guided femoral puncture and percutaneous arterial closure devices has reduced access site bleeding with a progressive improvement after the first 6 months learning period.